Economic development facets and their interrelation - Jaroslav Gonos; Daniela Hrehová; Katarína Čulková (Entrepreneurship and Sustainability Issues, 2022)
For many years, people have been trying to examine the factors that affect life in the country in which they live. Many procedures and methodologies have emerged into the help to measure individual aspects of life. One of them is GDP. But even though it is the most used of them, it focuses mainly on the economic side of life and ignores other factors that affect the lives of people in a given country. The aim of this paper is to identify the degree of connection between the development of the macroeconomic indicator of GDP and the index of economic freedom for the Slovak Republic. Based on the analysis of their development, components and impacts on the country, their main advantages and disadvantages will be determined, as well as their effectiveness compared to GDP. As no indicator can cover all areas, each of them looks at the same issue from a different angle, so to get a more comprehensive view of a country, it is not appropriate to focus on just one of them.